An exploration of barriers to insulin initiation for physicians in Japan: findings from the Diabetes Attitudes, Wishes And Needs (DAWN) JAPAN study. - Hitoshi Ishii; Yasuhiko Iwamoto; Naoko Tajima (PLoS ONE, 2012)
OBJECTIVE: Insulin is recommended as an appropriate treatment in type 2 diabetes patients with suboptimal glycemic control; however, its initiation is often delayed. We therefore conducted the DAWN (Diabetes Attitudes, Wishes and Needs) JAPAN study in an attempt to identify specific patient- and physician-related factors which contribute to delay of insulin initiation among Japanese patients with diabetes. In this report, we explored barriers for physicians which prevent timely insulin initiation. METHODS: The DAWN JAPAN study is a multicenter, questionnaire-based survey, conducted between 2004 and 2005. Participating physicians were categorized as follows based on their expertise: Japan Diabetes Society (JDS) certified specialists (n = 77), JDS-affiliated physicians (n = 30), and non-JDS-affiliated physicians (n = 27). To assess physician barriers to insulin initiation, we have used a newly developed 27- item questionnaire. RESULTS: The mean age of patients (n = 11,656) treated by participating physicians was 64.1 years. The mean duration of diabetes was 121.6 months, and their mean HbA1c was 7.5%. Insulin was used in 27.4% of total patients. With regard to physician barriers to insulin initiation, the biggest differences in concerns expressed by JDS-certified specialists and non-JDS-affiliated physicians were observed in the following items with statistical significance: "I do not have staff (nurse, pharmacists) who can assist with explanations" (1.3% vs 55.5%, respectively), "I have concerns about the use of insulin therapy in elderly patients" (38.1% vs 81.5%), and "It is difficult to provide guidance and education on insulin injection to patients" (16.9% vs 55.5%). The mean HbA1c at which physicians responded they would recommend insulin to their patients was 8.7%; however, they would reduce this level to 8.2% if they themselves required insulin. CONCLUSIONS: Our results demonstrated that physicians have concerns about insulin use, and suggested that their concerns can lead to delay of insulin initiation.